2020
DOI: 10.3390/cells9040823
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Metabolic Flexibility in Skeletal Muscle of Rat Fed with a High-Fat Diet Is Recovered by Individual CLA Isomer Supplementation via Converging Protective Mechanisms

Abstract: Energy balance, mitochondrial dysfunction, obesity, and insulin resistance are disrupted by metabolic inflexibility while therapeutic interventions are associated with improved glucose/lipid metabolism in skeletal muscle. Conjugated linoleic acid mixture (CLA) exhibited anti-obesity and anti-diabetic effects; however, the modulatory ability of its isomers (cis9, trans11, C9; trans10, cis12, C10) on the metabolic flexibility in skeletal muscle remains to be demonstrated. Metabolic inflexibility was induced in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 90 publications
2
15
0
Order By: Relevance
“…Several data suggest that also in the brain some of the effects exerted by CLA can be ascribed to its activation of PPARα. In fact, we have previously shown that PPARα activation by synthetic agonists increased PEA and OEA biosynthesis, as we also showed in liver and muscle in vivo ( Melis et al, 2013a ; Trinchese et al, 2018 ; Trinchese et al, 2020 ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Several data suggest that also in the brain some of the effects exerted by CLA can be ascribed to its activation of PPARα. In fact, we have previously shown that PPARα activation by synthetic agonists increased PEA and OEA biosynthesis, as we also showed in liver and muscle in vivo ( Melis et al, 2013a ; Trinchese et al, 2018 ; Trinchese et al, 2020 ).…”
Section: Introductionsupporting
confidence: 77%
“…OEA reduces food intake and body weight gain in obese rats ( Fu et al, 2005 ), stimulates lipolysis and FA oxidation ( Guzman et al, 2004 ), reduces the content of triacylglycerol (TAG) in both the liver and adipose tissue ( Guzman et al, 2004 ). All of these properties may be attributed to CLA ability to activate specific receptors such as peroxisome proliferator-activated receptors (PPAR) α, β/δ and AMP-activated protein kinase (AMPK) ( Trinchese et al, 2020 ). Despite the high brain expression of PPARβ and its possible role in regulating the metabolism of FAs and/or cholesterol, in inflammation processes and antioxidant mechanisms brain ( Hall et al, 2008 ), very little is known nowadays about how CLA regulates this nuclear receptor in the healthy and diseased brain.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK modulates cell metabolism based on the availability of nutrients and their capacity to produce ATP through mitochondrial oxidative phosphorylation. Chronic low-grade inflammation induced by obesity reduces AMPK activity in multiple tissues including skeletal muscle [ 18 , 19 , 20 ], liver [ 21 , 22 , 23 ] and adipose tissue [ 23 , 24 ], with a mechanism still partly unknown but probably involving altered mitochondrial fatty acid oxidation.…”
Section: Overnutrition and Altered Energy Homeostasismentioning
confidence: 99%
“…Thus, altered mitochondrial functions are part of the wide spectrum of metabolic changes induced by overnutrition-dependent low-grade inflammation [ 18 , 21 ]. In particular, mitochondrial dysfunction in liver and skeletal muscle leads to reduced FAs oxidation, impaired glucose homeostasis, increased ectopic lipid accumulation and decreased insulin sensitivity [ 15 , 19 ]. This is a hallmark of IR and type 2 diabetes [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Mitochondria Dysfunctions Oxidative Stress and Inflammatmentioning
confidence: 99%
See 1 more Smart Citation